Mental Health Quality in the Elderlyental Health Quality in the Elderly - Fadlih, Andi Muhammad; Ihsan, Andi (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The deterioration of mental health is a common phenomenon typically seen by the elderly. This condition can be mitigated or suppressed by augmenting physical activity. This study aimed to ascertain the correlation between physical activity and mental health quality in the senior population. Materials and methods. The research employed a cross-sectional design utilizing a cluster sampling technique involving 104 older individuals. The study sample mostly consisted of senior women aged 60-75 years, possessing diverse educational levels, marital statuses, and lacking chronic conditions. Results. The study's results indicated a correlation between physical activity levels and mental health in the elderly (p = 0.000; α = 0.05). Elderly caregivers are anticipated to mitigate mental health deterioration by enhancing physical activity through exercise. Conclusion. Moreover, additional research is anticipated to explore the intensity, duration, frequency, and various forms of physical exercise beneficial for enhancing or at least sustaining mental health in the elderly, thereby providing an updated theoretical framework regarding the impact of physical activity on the mental well-being of older adults.